Long-Term Warm–Cold Phase Shifts in the Gerlache Strait, Western Antarctic Peninsula - Su, Zhiqiang; Zhang, Zhaoru; Zhu, Yiwu; Zhou, Meng (Frontiers in Marine Science, 2022)
The Gerlache Strait plays an important role for the transports of heat, nutrients, and primary producers between the northern West Antarctic Peninsula (WAP) and the continental shelf in the southern WAP. The means, seasonal variations, and long-term trends of currents in the Gerlache Strait are analyzed based on Acoustic Doppler Current Profiler (ADCP) data between 1999 and 2016 available from the Joint Archive for Shipboard ADCP (JASADCP) dataset. The results revealed that the mean currents between the sea surface and 300 m in the Gerlache Strait (known as the Gerlache Strait Current) were predominantly northeastward, associated with the northeastward intrusion of Modified Circumpolar Deep Water (MCDW). The variance ellipses of currents were in parallel to the principal axis of the strait. The currents reached the maximum during austral spring and summer and were minimum during austral winter. The long-term trends revealed that the mean currents were southwestward during austral fall or winter before 2005, and the northeastward currents increased between 1999 and 2011, weakened, and reversed between 2011 and 2016. The long-term shifts between warm and cold phases in the Gerlache Strait were associated with shifts between the dominance of northeastward and southwestward currents in the strait, which are respectively associated with the intrusion of warm MCDW in the south and the transport of cold water from the Bransfield Strait in the north.